Encyclopedia of genocide - Charny, Israel W. (Santa Barbara, Calif. ABC-CLIO, 1999)
Alphabetical entries define names, places, and events associated with genocide, and major sections deal with the Armenian genocide, the Holocaust, and the process, detection, denial, and prevention of genocide.
v.1. A-H -- v.2. I-Y.
Keywords: Genocide -- Encyclopedias